Astrocyte glucocorticoid receptor signalling restricts neuronal plasticity - Bruno Gegenhuber; Takuma Sonoda; Lisa Traunmüller; Christopher P. Davis; Shon A. Koren; Eric C. Griffith; Chinfei Chen; Michael E. Greenberg (Nature, 2026)
Abstract Sensory experience refines neural circuits during critical periods of postnatal development 1–3 . Although neuronal activity is known to orchestrate the circuit wiring that underlies this process 4,5 , the environmental cues that restrain developmental plasticity as animals mature are less clear. Here we examine the experience-dependent maturation of the mouse primary visual cortex across postnatal development using paired single-cell transcriptomic and chromatin accessibility sequencing. In addition to identifying the activity-dependent gene programs that emerge within each cortical cell type, we find that light exposure drives astrocyte maturation through cell-type-specific recruitment of the glucocorticoid receptor (encoded by Nr3c1 ) to chromatin. Astrocyte glucocorticoid receptor signalling activates an extensive gene regulatory program that is partially conserved in human brain development and promotes maturation processes that may regulate critical period closure. Collectively, these findings reveal that astrocyte glucocorticoid receptor signalling restricts neuronal plasticity. Glucocorticoid regulation of astrocyte maturation may also contribute to the effects of early-life stress across the brain, and the disruption of this process may increase susceptibility to neuropsychiatric disease.